Influence of Simulated Golf Cart Traffic and Nitrogen Rate on Buffalograss Quality - E. Alderman; J. Hoyle; J. Fry; S. Keeley (Kansas Agricultural Experiment Station Research Reports, 2015)
Application of 2 and 3 lb N/1,000 ft2resulted in acceptable buffalograss quality when subjected to simulated golf cart traffic. Across all fertilizer treatments, traffic rates of 8 and 16 passes per week resulted in unacceptable quality ratings for the study duration.
Keywords: turfgrass; golf cart traffic; nitrogen; buffalograss; Buchloe dactyloides (Nutt.) Engelm; fertilizer; fertility management